2019
DOI: 10.1039/c8mh00946e
|View full text |Cite
|
Sign up to set email alerts
|

Identifying glioblastoma margins using dual-targeted organic nanoparticles for efficient in vivo fluorescence image-guided photothermal therapy

Abstract: Dual-targeted organic nanoparticles efficiently target the margin of glioblastoma and successfully suppress the tumour growth through photothermal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 31 publications
0
61
0
Order By: Relevance
“…Conventional GBM treatments are often limited by their brain‐targeted delivery efficiency due to the presence of blood–brain barrier (BBB) and blood–brain tumor barrier (BBTB) . In GBM at the early stage, BBB acts as the major barrier for brain targeted delivery and the protector for growth of tumor cells .…”
Section: Resultsmentioning
confidence: 99%
“…Conventional GBM treatments are often limited by their brain‐targeted delivery efficiency due to the presence of blood–brain barrier (BBB) and blood–brain tumor barrier (BBTB) . In GBM at the early stage, BBB acts as the major barrier for brain targeted delivery and the protector for growth of tumor cells .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, an ideal organic PTA should also possess good photothermal conversion efficiency, high photostability and photothermal stability, precise lesion site accumulation, and more importantly, simultaneous imaging (e.g., fluorescent and photoacoustic) and PTT capabilities. AIE‐active PTAs ( Scheme ) can be ideal alternatives, and have shown good performance in image‐guided PTT 111c,116e,123…”
Section: Image‐guided Therapymentioning
confidence: 99%
“…It has been hypothesized that combining PAI and PTT together will be a more effective strategy for cancer theranostics 116e,123b,c. For example, Cai et al123b reported that the introduction of propeller AIE units could significantly enhance PA signals and photothermal conversion efficiencies. The NIR‐absorbing/fluorescent (724/870 nm) compound BTPETTQ was obtained by connecting a TTQ core with two propeller AIE‐active TPE units.…”
Section: Image‐guided Therapymentioning
confidence: 99%
See 2 more Smart Citations